Teacher’s Aggression: Modern Approaches to Studying and Prevention - O. M. Dolidovich; A. A. Mashanov; N. A. Goncharevich; A. A. Sharashkina (Научный диалог)
The results of analysis of modern scientific approaches to the study and prevention of pedagogical aggression are presented. The relevance of the work is caused by a wide spread of aggressive forms of behaviour in society, including the educational environment. After reviewing the theoretical and empirical psychological and pedagogical works of Russian scientists, the authors found that most researchers see the reasons for pedagogical aggression in professional deformation of teacher’s personality. It is noted that it may occur at different stages of development of a specialist, affect the structure of personality, is detrimental to its activity and behaviour. It is shown that at the same time, other researchers focus on the destructive manifestations of pedagogical discourse, considering the aggression of the teacher an integral part thereof and is evident in the evaluation of actions aimed at changing the subjectivity of a student. The authors propose the idea of complex psychological support of teacher’s action as ways of prevention and correction of pedagogical aggression, the purpose of which should be assistance in overcoming various kinds of difficulties of personal and professional character. It is indicated that the work on forming the culture of behavior and speech etiquette of teachers and students of pedagogical universities, learning the techniques of public communication and effective response in conflict situations have serious importance.